Degradability and gas production of diets enriched with additives in cattle or sheep inoculum - Freitas Prado, Tayrone; Souza França, Aldi Fernandes de; Ulhoa, Cirano José; de Oliveira, Leonardo Guimarães; Cysneiros, Cristine dos Santos Settimi; de Oliveira, Graciele Araújo; Staciarini Corrêa, Daniel; Nassar Ferreira, Reginaldo (International Journal of Advanced Engineering Research and Science, 2021)
The study of ruminal kinetics of feedstuffs and the influence of feed additives on degradability and gas production can contribute to the formulation of more efficient diets. This study proposes to examine cumulative gas production from rumen fermentation and the in vitro degradability of diets containing maize and cottonseed cake enriched with amylolytic enzyme, protected lysine, lysophospholipids or protected methionine. In the degradability trial, the samples were incubated in anaerobic medium for 0, 3, 6, 12, 24 and 48 h, at 39 °C. In vitro gas production was determined at the incubation times of 3, 6, 9, 12, 16, 24, 32, 48 and 72 h, and the use of cattle and sheep ruminal fluid was compared. The inclusion of lysophospholipid increased (P<0.05) the degradability of dry matter in the diet, whereas the addition of protected methionine reduced this variable. Gas production was greater in sheep inoculum up to 48 h of fermentation, and no differences were detected at 72 h. The amylolytic enzyme increased the gas production only up to 24 h of fermentation. After this time, none of the tested additives increased gas production.